Parental intention to vaccinate adolescents with HPV vaccine in selected communities in Ibadan, Southwest Nigeria: an application of Integrated Behavioral Model (2022)
Parents have important roles to play for adolescents to get the human papillomavirus (HPV) vaccine, an effective measure in the prevention of cervical and other HPV-related cancers. It is important to understand the intention of parents to have their adolescents vaccinated for optimal uptake of the vaccine in Nigeria. This study investigated the intention of parents in five selected communities to get their adolescents vaccinated with HPV vaccine in Ibadan, Nigeria using the Integrated Behavioral Model (IBM). Cross sectional study design was employed and 678 parents were interviewed. Pearson correlation, chi-square test and multiple regression were used for data analysis at α = 0.05. Mean age of the parents was 42.5 ± 10.0 years and 230(33.9%) were males. Almost all of the parents (96.8%) had the intention to vaccinate their adolescents with HPV vaccine. This intention was significantly correlated with experiential attitude (r = 0.74, p = <.01), instrumental attitude (r = 0.33, p = <.01), injunctive norm (r = 0.39, p = <.01), descriptive norm (r = 0.32, p = <.01), perceived control (r = 0.32, p = <.01) and self-efficacy (r = 0.46, p ≤ .01). A higher proportion of parents older than 65 years significantly had no intention to vaccinate their adolescents with HPV vaccine. Intention to vaccinate adolescents with HPV vaccine was predicted by experiential attitude (OR = 0.88, 95% CI: 0.80– 0.95), personal agency (OR = 0.22, 95% CI: 0.15–0.29) and injunctive norm (OR = 0.08, 95% CI: 0.02–0.13). Parental intention to vaccinate adolescents with HPV vaccine was high among the parents in this study. The reluctance of older parents about HPV vaccine for adolescents requires further investigation.